Ut Once More: The Sentence as the Key Functional Unit of Translation - Zhu, Chunshen (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1999)
AbstractText linguistics enables translators to [201c]climb up,[201d] to work more effectively from the level of text with [201c]textual judicial authority.[201d] It should enable them to [201c]look down[201d] as well at lower units as functional units. Technically, discussions of translation often treat localized passages rather than full texts. The notion of Unit of Translation (UT), once defined, is thus useful for bridging the technical gap between the full text and its components in describing relationships involved in a translation, and looking at a localized passage's potential accountability to the whole text. This article approaches the issue of UT from the point of view of division of labour between short-term and long-term memory in translating, and defines the UT functionally as textual unit instead of language unit which maintains its textual integrity by performing three functions, viz. syntatic bearer, information carrier, and stylistic marker. Text translation thus boils down to the preservation of the textual integrity of each UT not in syntactic form but in function, given the necessary rank-shifts in the process. To that end, it argues, the key functional UT can be set at the level of sentence. The article is a revised version of the first part of Zhu (1996a).